Magistrates-elect and their potestas contionandi in the Late Roman Republic - Pina Polo, Francisco (Historia: zeitschrift für alte geschichte: revue d'histoire ancienne, 2016)
The ancient sources mention speeches being delivered in the late Republic in contiones by both consuls-elect and tribunes of the plebs designate. It has usually been assumed that as magistrates-elect they did not have the right to summon a popular assembly. In this paper it is suggested that magistrates-designate – or at least some of them – had this privilege. This should be understood in the more general framework in which the designati played a political and institutional role during the late Republic.